Boyfriend lessons - Sasson, Sophia (Harlequin desire, 2022)
Shy Lone Star heiress Caitlyn Lattimore is eager to ditch her wallflower status. So when her best friend playfully suggests she practice dating, Caitlyn goes one further. She asks friend of a friend Dev Mallik to give her boyfriend lessons. The spark between them soon turns fun into fire. But is Caitlyn setting herself up for heartbreak? Because Dev's exacting parents want just the right woman for their son--and they aren't so sure she's the one...